2011
DOI: 10.1016/s1474-4422(11)70148-x
|View full text |Cite
|
Sign up to set email alerts
|

APOE genotype and extent of bleeding and outcome in lobar intracerebral haemorrhage: a genetic association study

Abstract: SUMMARY Background APOE alleles ε2/ε4 increase risk of intracerebral hemorrhage (ICH) in the lobar regions, presumably through their influence on risk of cerebral amyloid angiopathy. We investigated whether these variants also associate with ICH severity, specifically larger ICH volume at presentation. Methods We initially investigated the association of ε2/ε4 with ICH volume and outcome in a Discovery sample of 865 individuals of European ancestry. Replication was completed in two samples, comprising 946 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 28 publications
(35 reference statements)
4
111
0
4
Order By: Relevance
“…8,9 Whether the epsilon polymorphism is also associated with an increased risk of ischemic stroke and MRI markers of CVD is unclear.…”
Section: -6mentioning
confidence: 99%
“…8,9 Whether the epsilon polymorphism is also associated with an increased risk of ischemic stroke and MRI markers of CVD is unclear.…”
Section: -6mentioning
confidence: 99%
“…The e2 allele is protective in Alzheimer's disease but associated with an increased risk of cerebral amyloid angiopathy-related lobar ICH. 61,62 The relationship between markers of SVD and APOE genotype was assessed by a meta-analysis of 42 cross-sectional or longitudinal studies. APOE e4 was associated with an increased burden of both WMH and microbleeds, and APOE e2 was associated with an increased WMH burden.…”
Section: Apolipoprotein Ementioning
confidence: 99%
“…The apolipoprotein E ε2 allele is associated with larger hematomas, which appears to explain its effect on outcome [15]. The relation between oral anticoagulation use and baseline hematoma volume is unclear; some studies have shown increased baseline volumes [16,17], whereas others have not [15,18].…”
Section: Initial Hematomamentioning
confidence: 99%
“…The observed increase is most likely due to the increased use of warfarin by patients with atrial fibrillation [58]. The use of warfarin at the time of ICH is associated with hematoma expansion [16,18] and increased mortality [15][16][17]59].…”
Section: Anticoagulation Reversalmentioning
confidence: 99%